Religious discourse, power and the public - Degenaar, Johan (Neotestamentica, 1997)
Three kinds of discourse are distinguished: premodern, modern, postmodern. The emphasis is placed on postmodernism by mentioning the (positive) characteristics of (affirmative) postmodernism. This is followed by a conceptual analysis of the main concepts entailed by the theme of the paper, namely, rhetoric, language/discourse, religion, power and the public. The relevance of the theme is demonstrated by relating religious discourse to the notions of secularisation, plurality (with special reference to multi-culturalism), intertextuality, ideology and public opinion.